Melatonin and its derivatives counteract the ultraviolet B radiation‐induced damage in human and porcine skin ex vivo. Issue 2 (21st May 2018) - Skobowiat, Cezary; Brożyna, Anna A.; Janjetovic, Zorica; Jeayeng, Saowanee; Oak, Allen S. W.; Kim, Tae‐Kang; Panich, Uraiwan; Reiter, Russel J.; Slominski, Andrzej T.
Abstract: Melatonin and its derivatives ( N 1 ‐acetyl‐ N 2 ‐formyl‐5‐methoxykynurenine [AFMK] and N ‐acetyl serotonin [NAS]) have broad‐spectrum protective effects against photocarcinogenesis, including both direct and indirect antioxidative actions, regulation of apoptosis and DNA damage repair; these data were primarily derived from in vitro models. This study evaluates possible beneficial effects of melatonin and its active derivatives against ultraviolet B (UVB)‐induced harm to human and porcine skin ex vivo and to cultured HaCaT cells. The topical application of melatonin, AFMK, or NAS protected epidermal cells against UVB‐induced 8‐OHdG formation and apoptosis with a further increase in p53 ser15 expression, especially after application of melatonin or AFMK but not after NAS use. The photoprotective action was observed in pre‐ and post‐UVB treatment in both human and porcine models. Melatonin along with its derivatives upregulated also the expression of antioxidative enzymes after UVB radiation of HaCaT cells. The exogenous application of melatonin or its derivatives represents a potent and promising tool for preventing UVB‐induced oxidative stress and DNA damage. This protection results in improved genomic, cellular, and tissue integrity against UVB‐induced carcinogenesis, especially when applied prior to UV exposure. In addition, our ex vivo experiments provide fundamental justification for further testing the clinical utility of melatonin and metabolites as protectors again UVB in human subjects. Our ex vivo data constitute the bridge between vitro to vivo translation and thus justifies the pursue for further clinical utility of melatonin in maintaining skin homeostasis.